2014
DOI: 10.1007/s11096-014-9951-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement in medication safety in hospital: an exploratory study

Abstract: Background Medication errors are common in hospital inpatients. While many interventions have been proposed to address these problems, few have been shown to have significant benefits. A complementary approach is to facilitate greater involvement of patients with their inpatient medication. However, there is relatively little research in this area and it is not known which interventions lead to improved healthcare outcomes. Work is therefore needed to investigate the roles that healthcare professionals and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 17 publications
1
55
1
2
Order By: Relevance
“…There may be a gender specific and generational attitude difference in patient response to our questionnaire: the demographic data presented in figures 2 and 3 and table 2 broadly concur with findings expressed by Professor Vincent’s team from London12 and in the exploratory study on medication safety by Mohsin-Shaikh e t al 22 indicating that males and those over 60 years of age showed significantly lower desire for involvement. It is unclear why these groups are less engaged and we can only postulate that older people, who may be already cognitively inhibited, also come from a generation that believes that doctors ‘know best’ and thus, do not feel empowered to challenge healthcare professionals.…”
Section: Discussionsupporting
confidence: 84%
“…There may be a gender specific and generational attitude difference in patient response to our questionnaire: the demographic data presented in figures 2 and 3 and table 2 broadly concur with findings expressed by Professor Vincent’s team from London12 and in the exploratory study on medication safety by Mohsin-Shaikh e t al 22 indicating that males and those over 60 years of age showed significantly lower desire for involvement. It is unclear why these groups are less engaged and we can only postulate that older people, who may be already cognitively inhibited, also come from a generation that believes that doctors ‘know best’ and thus, do not feel empowered to challenge healthcare professionals.…”
Section: Discussionsupporting
confidence: 84%
“…Prior research has shown that patients are interested in engaging more in safety efforts [31][32][33] and that physicians, nurses, and other health care professionals support increasing such patient involvement. 31,32 However, interpersonal, intrapersonal, and cultural barriers to patient involvement in safety initiatives exist.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 However, interpersonal, intrapersonal, and cultural barriers to patient involvement in safety initiatives exist. 34 For instance, patients appear to be less comfortable with safety efforts that require them to engage in what they perceive as challenging behaviors (eg, notifying physicians/nurses of errors) and conversely more comfortable with efforts that involve non challenging behaviors (eg, reporting an error to a reporting system).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a paucity of evidence to support patient focused interventions within AMS programmes, a growing body of literature is emerging that describes physician's and patient's desire for increased collaboration in the decision-making process surrounding the prescription of medications within secondary care 21. However, there is currently no specific evidence describing patients’ experiences of infection management and antimicrobial prescribing within this setting.…”
Section: Introductionmentioning
confidence: 99%